Prenatal diagnosis of Down syndrome: A 13-year retrospective study - Ana Vičić; Tomislav Hafner; Ivanka Bekavac Vlatković; Petra Korać; Dubravko Habek; Feodora Stipoljev (Elsevier, 2017)
Objective: The aim of this study is to summarize the experience on prenatal diagnosis of Down syndrome. Materials and methods: The study includes a retrospective data analysis of 157 prenatally detected cases of Down syndrome, routinely diagnosed among 6448 prenatal investigations performed during a 13-year period (2002-2014) in a single tertiary center. Results: The prevalence of diagnosed Down syndrome cases was 2.4%. Maternal age alone was indication for prenatal diagnosis in 47 cases (45.2%), increased first-/second-trimester biochemical screening test in 34 cases (21.7%), abnormal ultrasound examination in 69 cases (43.9%), positive familial history for chromosomal abnormalities in four cases, and high risk for trisomy 21 revealed by cell-free DNA testing in three cases. Ultrasound anomalies were present in total of 94 fetuses (59.8%). The most common abnormality was cystic hygroma found in 46 cases (29.3%). A regular form of Down syndrome (trisomy 21) was found in 147 cases (93.6%), Robertsonian translocation in six cases (3.8%), and mosaic form in four cases (2.6%). Conclusion: In prenatal diagnosis of Down syndrome noninvasive screening methods are important for estimation of individual risks, in both, young population of woman and older mothers, while conventional and molecular cytogenetic methods are essential for definite diagnosis and proper genetic counseling.